Guselkumab in Patients With Moderately to Severely Active Ulcerative Colitis: QUASAR Phase 2b Induction Study - Peyrin-Biroulet, Laurent; Allegretti, Jessica R; Rubin, David T; Bressler, Brian; Germinaro, Matthew; Huang, Kuan-Hsiang Gary; Shipitofsky, Nicole; Zhang, Hongyan; Wilson, Rebbecca; Han, Chenglong; Feagan, Brian G; Sandborn, William J; et al. (Gastroenterology, 2023)
BACKGROUND & AIMS: The QUASAR Phase 2b Induction Study evaluated the efficacy and safety of guselkumab, an interleukin-23p19 subunit antagonist, in patients with moderately to severely active ulcerative colitis (UC) with prior inadequate response and/or intolerance to corticosteroids, immunosuppressants, and/or advanced therapy. METHODS: In this double-blind, placebo-controlled, dose-ranging, induction study, patients were randomized (1:1:1) to receive intravenous guselkumab 200 or 400 mg or placebo at weeks 0/4/8. The primary endpoint was clinical response (compared with baseline, modified Mayo score decrease ≥30% and ≥2 points, rectal bleeding subscore ≥1-point decrease or subscore of 0/1) at week 12. Guselkumab and placebo week-12 clinical nonresponders received subcutaneous or intravenous guselkumab 200 mg, respectively, at weeks 12/16/20 (uncontrolled study period). RESULTS: The primary analysis population included patients with baseline modified Mayo scores ≥5 and ≤9 (intravenous guselkumab 200 mg, n = 101; 400 mg, n = 107; placebo, n = 105). Week-12 clinical response percentage was greater with guselkumab 200 mg (61.4%) and 400 mg (60.7%) vs placebo (27.6%; both P < .001). Greater proportions of guselkumab-treated vs placebo-treated patients achieved all major secondary endpoints (clinical remission, symptomatic remission, endoscopic improvement, histo-endoscopic mucosal improvement, and endoscopic normalization) at week 12. Among guselkumab week-12 clinical nonresponders, 54.3% and 50.0% of patients in the 200- and 400-mg groups, respectively, achieved clinical response at week 24. Safety was similar among guselkumab and placebo groups. CONCLUSIONS: Guselkumab intravenous induction was effective vs placebo in patients with moderately to severely active UC. Guselkumab was safe, and efficacy and safety were similar between guselkumab dose groups. CLINICALTRIALS: gov number: NCT04033445.
Keywords: ulcerózní kolitida; výsledek terapie; Colitis, Ulcerative; dvojitá slepá metoda; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; QUASAR; Interleukin-23p19 Subunit Antagonist; Advanced Therapy; lidé; Double-Blind Method; Immunosuppressive Agents; Ulcerative Colitis; indukce remise; Humans; imunosupresiva; Remission Induction